2021
DOI: 10.1186/s12936-021-03589-2
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis and activation of bone marrow‐derived macrophages by Plasmodium falciparum gametocytes

Abstract: Background The innate immune response against various life cycle stages of the malaria parasite plays an important role in protection against the disease and regulation of its severity. Phagocytosis of asexual erythrocytic stages is well documented, but little and contrasting results are available about phagocytic clearance of sexual stages, the gametocytes, which are responsible for the transmission of the parasites from humans to mosquitoes. Similarly, activation of host macrophages by gamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…TNF-α and IFN-γ, for instance, have both previously been demonstrated to be involved with gametocyte killing in the mammalian host ( 68 , 69 ), with TNF-α being shown to impact transmission in rodent models ( 70 ). Macrophages in culture have been shown to phagocytose gametocytes and produce TNF-α, MIP-2, and NO in response to late-stage gametocytes, suggesting innate immune involvement in controlling sexual stage parasites ( 71 ). In our network analyses, plasma IL-17 and IL-10 in baso (−) mice at 3 d p.i.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α and IFN-γ, for instance, have both previously been demonstrated to be involved with gametocyte killing in the mammalian host ( 68 , 69 ), with TNF-α being shown to impact transmission in rodent models ( 70 ). Macrophages in culture have been shown to phagocytose gametocytes and produce TNF-α, MIP-2, and NO in response to late-stage gametocytes, suggesting innate immune involvement in controlling sexual stage parasites ( 71 ). In our network analyses, plasma IL-17 and IL-10 in baso (−) mice at 3 d p.i.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods are frequently employed to detect phagosome, as well as phagolysosome formation. Giemsa staining has been traditionally used to observe such phenomena in numerous cell lines [ 18 ]. However, due to monochrome staining, accurately differentiating between amoebal mitochondria from E. coli was somewhat problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported the elevation of NO in blood upon Plasmodium infection in children with malarial anemia [ 144 , 145 ]. Interestingly, recent data show that P. falciparum gametocytes are phagocytosed by immortalised mouse BM-derived macrophages and late gametocytes initiate the production of NO, cytokines, and chemokines [ 146 ]. Although these data have to be confirmed in a more physiological human setting, they suggest that gametocytes may stimulate the secretion of erythropoiesis-inhibiting factors by macrophages constituting the erythroblastic islands, which are the specialised niches for erythropoiesis.…”
Section: Human and Parasite Factors Affecting Erythropoiesismentioning
confidence: 99%